2018
DOI: 10.1172/jci.insight.98864
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal TNFR2 promotes the development of polyarthritis and comorbid heart valve stenosis

Abstract: Mesenchymal TNF signaling is etiopathogenic for inflammatory diseases such as rheumatoid arthritis and spondyloarthritis (SpA). The role of Tnfr1 in arthritis has been documented; however, Tnfr2 functions are unknown. Here, we investigate the mesenchymal-specific role of Tnfr2 in the TnfΔARE mouse model of SpA in arthritis and heart valve stenosis comorbidity by cell-specific, Col6a1-cre-driven gene targeting. We find that TNF/Tnfr2 signaling in resident synovial fibroblasts (SFs) and valvular interstitial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Overall, these mice could be an advantageous SpA mouse model as they spontaneously mimic the complexity of human SpA in a tmTNF-driven manner. The main findings of the axial pathology, as well as the new bone formation observed in the TgA86 mice, could differentiate this model from the other mouse or human TNF overexpressing mice [16][17][18][19]21] that express soluble and transmembrane TNF signaling through both TNFR1 and TNFR2 and have been reported to develop only peripheral arthritis. This could suggest that tmTNF-TNFR2 signaling may have a central role in the development of SpA, a hypothesis also supported by the high levels of tmTNF detected in human SpA patients [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these mice could be an advantageous SpA mouse model as they spontaneously mimic the complexity of human SpA in a tmTNF-driven manner. The main findings of the axial pathology, as well as the new bone formation observed in the TgA86 mice, could differentiate this model from the other mouse or human TNF overexpressing mice [16][17][18][19]21] that express soluble and transmembrane TNF signaling through both TNFR1 and TNFR2 and have been reported to develop only peripheral arthritis. This could suggest that tmTNF-TNFR2 signaling may have a central role in the development of SpA, a hypothesis also supported by the high levels of tmTNF detected in human SpA patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory cytokine tumor necrosis factor alpha (TNF-α) is a key pathogenic factor involved in the development of SpA, with evidence stemming primarily from the significant therapeutic effect of TNF-blocking agents that, when administered early on in the development of the disease, can alleviate SpA symptoms [ 12 15 ]. It has been previously shown that overexpression of mouse TNF through the deletion of AU-rich elements in its 3′UTR, leads to the development of destructive polyarthritis, sacroiliitis, enthesitis, Crohn’s-like IBD, and aortic valve inflammation, however, without evidence of new bone formation [ 16 , 17 ]. Similarly, mouse models overexpressing human TNF [ 18 , 19 ] have been shown to develop spontaneous arthritis also missing however evidence of new bone formation, which is the main feature of SpA.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these mice could be an advantageous SpA mouse model as they spontaneously mimic the complexity of human SpA in a tm-TNF-driven manner. The main findings of the axial pathology, as well as the new bone formation observed in the TgA86 mice could differentiate this model from the other mouse or human TNF overexpressing mice (16)(17)(18)(19)21) that express soluble and transmembrane TNF signaling through both TNFR1 and TNFR2 and have been reported to develop only peripheral arthritis. This could suggest that tmTNF-TNFR2 signaling may have a central role in the development of SpA, a hypothesis also supported by the high levels of tmTNF detected in human SpA patients (34).…”
Section: Discussionmentioning
confidence: 91%
“…Overall, these mice could be an advantageous SpA mouse model as they spontaneously mimic the complexity of human SpA in a tm-TNF-driven manner. The main ndings of the axial pathology, as well as the new bone formation observed in the TgA86 mice could differentiate this model from the other mouse or human TNF overexpressing mice (16)(17)(18)(19)21) that express soluble and transmembrane TNF signaling through both TNFR1 and TNFR2 and have been reported to develop only peripheral arthritis. This could suggest that tmTNF-TNFR2 signaling may have a central role in the development of SpA, a hypothesis also supported by the high levels of tmTNF detected in human SpA patients (37).…”
Section: Discussionmentioning
confidence: 92%
“…The pro-in ammatory cytokine Tumor Necrosis Factor alpha (TNF-α) is a key pathogenic factor involved in the development of SpA, with evidence stemming primarily from the signi cant therapeutic effect of TNF-blocking agents that, when administered early on in the development of the disease, can alleviate SpA symptoms (12)(13)(14)(15). It has been previously shown that overexpression of mouse TNF through the deletion of AU-rich elements in its 3'UTR, leads to the development of destructive polyarthritis, sacroiliitis, enthesitis, Crohn's-like IBD and aortic valve in ammation, however without evidence of new bone formation (16,17). Similarly, mouse models overexpressing human TNF (18,19) have been shown to develop spontaneous arthritis also missing however evidence of new bone formation, which is the main feature of SpA.…”
Section: Introductionmentioning
confidence: 99%